Comparative effectiveness of posttreatment imaging modalities for Medicare patients with advanced head and neck cancer. Issue 4 (29th October 2020) - Morgan, Rustain L.; Eguchi, Megan M.; McDermott, Jessica; Mueller, Adam C.; Amini, Arya; Goddard, Julie A.; Trivedi, Premal S.; Karam, Sana D.
Abstract : Background: Persistent controversy exists with regard to how and when patients with head and neck cancer should undergo imaging after definitive therapy. The current study was conducted to evaluate whether the type of imaging modality used in posttreatment imaging impacts cancer‐specific survival for patients with advanced head and neck squamous cell carcinoma. Methods: A retrospective study of National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) program–Medicare‐linked data in patients with an advanced stage of the 3 most common head and neck malignancies (oral cavity, oropharynx, and larynx) was conducted. Hazard ratios and 95% CIs for cancer‐specific survival were estimated for patients diagnosed with any of these cancers between 2006 and 2015. Results: Significant improvement with regard to cancer‐specific survival was observed among patients with American Joint Committee on Cancer stage III and stage IVA laryngeal cancer who underwent positron emission tomography (PET) and/or computed tomography (CT) imaging during the first 6 months after receipt of definitive treatment (hazard ratio, 0.517; 95% CI, 0.33‐0.811) compared with those who underwent CT. There was a trend toward an improvement in cancer‐specific survival among patients with oral cavity or oropharyngeal malignancies who underwent PET/CT imaging, but it did not reach statistical significance. Conclusions: Compared with CT imaging, posttreatment imaging with PET was associated with improved survival in patients with advanced laryngeal carcinoma. Abstract : Persistent controversy exists regarding how and when patients with head and neck cancer should undergo imaging after receiving definitive therapy. The current study evaluates whether the type of imaging modality used in posttreatment imaging impacts cancer‐specific survival for patients with advanced head and neck squamous cell carcinoma and finds that, compared with computed tomography imaging, posttreatment imaging using positron emission tomography is associated with improved survival in patients with advanced laryngeal carcinoma.